Financial aspects of forming the image of the region as a tourist destination - Oveskov, O. V. (ТДАТУ, 2021)
А country’s image in the world and its role in international trade are largely determined by the state and level of competitiveness of the international tourism industry. Recently, international tourism has become an industry whose role in the international economy has grown significantly due to its rapid development. Therefore, the formation of a positive image of the region as a tourist destination will ensure the growth of external and internal tourist flows; additional inflows of investments in the region; creation of new jobs both directly in tourism and in related types of economic activity; additional receipts to local and state budgets; improving the quality of life of the local population and the like.
Keywords: tourist; financial aspects of the development of; image of the region